Pengaruh Kontrol Diri terhadap Perilaku Cyberbullying Pada Remaja - Fatma, Eliza Qotrunnadza Munawaroh; Agustina, Mirna Wahyu (Program Studi Psikologi Islam (IAIN) Kediri, 2023)
There are many phenomena of gadget users nowadays ranging from children to adults, if the use of gadgets is not controlled properly it will cause cases of cyberbullying, which will make teenagers in the future more vulnerable to bullying in cyberspace. This research was encouraged because there was data on an increase in cyberbullying from field data and news. The purpose of this study was to obtain correct information, to determine the effect of self-control on adolescent cyberbullying, the sample of this study was adolescents aged 13-18 years with a total of 384 respondents. The research measurement tools are the self-control scale and the cyberbullying scale. This study uses a comparative causal quantitative with a simple regression analysis technique using SPSS 23 For Windows. Based on the research results, it is known that there is a significant influence between self-control and cyberbullying with a value of p = 0.000 <0.05, with a value of R = 0.287.